2005
DOI: 10.1007/s10549-004-5168-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of breast screening among women with and without a family history of breast and/or ovarian cancer

Abstract: Screening was able to detect a large proportion of invasive breast cancers in women with a family history, indicating their potential to benefit from regular breast cancer screening. However, due to increased interval cancer rates, screening with one-year intervals may be important even in an older population of women with a family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…Our finding of higher incidence rates among women with positive family histories is consistent with at least two other incidence studies [17,27]. [17] cited a 2.28 increase in interval cancer rates within 12 months of screening among women with a strong family history of breast and/ovarian cancer (95% CI 0.97-5.34); an increase somewhat higher than that reported by [27] of 1.72 (95% CI 1.23-2.40) for women with a mother or sister diagnosed with breast cancer under 50 years of age compared with women without family history. One plausible explanation for elevated risk in women with family history is that these women confer greater overall breast cancer risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of higher incidence rates among women with positive family histories is consistent with at least two other incidence studies [17,27]. [17] cited a 2.28 increase in interval cancer rates within 12 months of screening among women with a strong family history of breast and/ovarian cancer (95% CI 0.97-5.34); an increase somewhat higher than that reported by [27] of 1.72 (95% CI 1.23-2.40) for women with a mother or sister diagnosed with breast cancer under 50 years of age compared with women without family history. One plausible explanation for elevated risk in women with family history is that these women confer greater overall breast cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…Other suggested risk factors for interval versus screen-detected cancer include having had previous breast surgery and history of benign breast disease [5,12]. Despite the well-established association between family history and breast cancer risk overall, there is mixed evidence as to whether having a positive family history predisposes a woman to having interval versus screen-detected cancer [2,9,13,[15][16][17]. It is also not well established as to whether risk for interval versus screen-detected cancer differs among racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…A non-significant trend towards a lower sensitivity was found in pre-menopausal as compared to post-menopausal women, after adjustment for age and breast density [13,19]. A family history of breast cancer, and especially a BRCA1/2 mutation carriership, has been reported to be associated with a decreased sensitivity of mammography [2,11,20,21].…”
Section: Introductionmentioning
confidence: 95%
“…17 Screening at 1-year intervals may remain important in older women with a positive family history to detect interval cancers. 18 Watson et al 19 found that similar to women in the general population, most women with a family history do not seem to experience high levels of anxiety associated with mammographic screening. The high self-reported mammography rate we found may be a reflection of partici- pants putting themselves in a favorable light when responding to questions or the combined work of providers and patients optimizing screening.…”
Section: Breast Cancer Family History Effectsmentioning
confidence: 99%